IMPLEMENTASI DIMENSI PROFIL LULUSAN TERHADAP PEMBENTUKAN KARAKTER SISWA DI UPT SPF SDN MATTOANGIN II - Andi Dwi Nuvriyanti; Sri Rahmayanti; Nuraeni; Suriani S; Burhan; Perry Irawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the research problem concerning how the implementation of graduate profile dimensions contributes to students’ character development from a philosophical perspective at UPT SPF SDN Mattoangin II, as well as the strategies, student responses, and challenges encountered during the process. The purpose of this study was to describe the implementation of graduate profile dimensions, analyze the strategies employed by teachers, and identify the supporting and inhibiting factors in students’ character development. This study employed a qualitative approach with a descriptive research design. The research subjects consisted of teachers and sixth-grade students selected through purposive sampling techniques. Data collection was conducted through observation, semi-structured interviews, and documentation. Data analysis was carried out descriptively to obtain an in-depth understanding of the phenomena being investigated. The findings revealed that the implementation of graduate profile dimensions had been integrated into the learning process through planning, implementation, and evaluation stages. The main strategies applied included modeling, habituation, and the use of active learning methods such as discussions and question-and-answer activities. Students demonstrated positive responses through behavioral changes, including increased discipline, responsibility, independence, cooperation skills, and the development of critical reasoning abilities. However, several challenges were identified, including the lack of consistency between school and home environments and the influence of digital media. The study concludes that the implementation of graduate profile dimensions provides a positive impact on students’ character development. Nevertheless, further reinforcement is still needed through stronger collaboration between schools and parents, as well as the improvement of students’ digital literacy.